A third (booster) dose of the inactivated SARS-CoV-2 vaccine elicits immunogenicity and T follicular helper cell responses in people living with HIV - Lv, Zhengchao; Lv, Songqin; Li, Qin; Xia, Yafei; Feng, Zaineng; Zhang, Haohong; Yang, Haihao; Wu, Zhao; Zou, Nanting; Mo, Qingyan; Gu, Qianlan; Ying, Sai; et al. (Frontiers in Immunology, 2023)
Introduction: This research was designed to explore the immunogenicity of a booster dose of an inactivated severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccine in people living with human immunodeficiency virus (HIV) and clarify the factors that affected the magnitude of anti-SARS-CoV-2 antibody concentrations. Materials and Methods: In a cohort comprising 34 people living with HIV (PLWH) juxtaposed with 34 healthy donors (HD), both groups were administered an additional dose of the analogous vaccine. The quantification of lymphocytes underwent assessment via flow cytometry. The concentrations of anti-SARS-CoV-2 antibody and Immunoglobulin G (IgG) were gauged utilizing the SARS-CoV-2 S protein neutralizing antibody Enzyme-Linked Immunosorbent Assay kit and the 2019-nCov IgG Chemiluminescent Immunoassay Microparticles, respectively. The correlation between laboratory markers and neutralizing antibodies, as well as IgG, was discerned using Spearman correlation analysis. Employing density gradient centrifugation, peripheral blood mononuclear cells from the subjects were extracted. Concurrently, the presence of memory T cells and T follicular helper cells were ascertained through flow cytometry. Results: In PLWH, there was a marked reduction in the expression of CD4 and B cells, accompanied by a discernibly diminished CD4/CD8 ratio. In line with our antecedent findings, a supplementary dose of inactivated SARS-CoV-2 vaccines conferred antibody positivity rates in PLWH analogous to those previously observed. This booster vaccine instigated a decrement in IgG concentrations and neutralizing antibodies, with the amplitude of this decline being substantially pronounced in PLWH compared to HD. Correlation analyses unveiled potent correlation between neutralizing antibody levels and the counts and proportion of CD4 cells. A congruent trend emerged concerning anti-SARS-CoV-2 IgG antibodies. Additionally, for those HIV-positive individuals characterized as weak or non-responders, there was a conspicuously attenuated expression of memory T cells and Tfh relative to HD. Discussion: PLWH manifested attenuated immunological reactions to a tertiary (booster) administration of inactivated SARS-CoV-2 vaccines, indicated by diminished concentrations of neutralizing antibodies and IgG. This could be attributed to the responsiveness of CD4 cells, particularly those of memory T and cTfh subsets. Such laboratory parameters, namely CD4 and cTfh cells, may serve as pivotal tools for surveilling the mechanisms culminating in synthesizing enduring and protective antibodies.